2015
DOI: 10.1016/j.jiph.2015.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of dengue infections in the Kassala state in the eastern part of the Sudan in 2011

Abstract: Dengue fever is a vector-borne disease that is transmitted to humans by infected Aedes aegypti mosquitoes. The eastern part of the Sudan is one of the regions that is affected by dengue virus circulation. In this study, we estimated the prevalence of dengue infections in the Kassala state in the eastern part of the Sudan. The study objective was to estimate the sero-prevalence of dengue IgG/IgM antibodies in the Kassala locality in 2011. This was a cross sectional community-based study that utilized a multi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
2
20
1
Order By: Relevance
“…However, only two studies were conducted to evaluate recent transmission of DENV in the locality of Kassala and not the whole State. A previous seroepidemiological survey for DENV IgM, using Panbio (DF IgG and IgM) ELISA kits, reported a very low prevalence of 0.6% among residents of Kassala locality [16]. However, the underestimated prevalence of DENV IgM was attributed to the limitation of the ELISA assay to accurately detect IgM in sera from the study participants.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, only two studies were conducted to evaluate recent transmission of DENV in the locality of Kassala and not the whole State. A previous seroepidemiological survey for DENV IgM, using Panbio (DF IgG and IgM) ELISA kits, reported a very low prevalence of 0.6% among residents of Kassala locality [16]. However, the underestimated prevalence of DENV IgM was attributed to the limitation of the ELISA assay to accurately detect IgM in sera from the study participants.…”
Section: Introductionmentioning
confidence: 85%
“…In a previous report the prevalence of DEMV-IgM seropositivity, during disease outbreak in Kassala State, was reported to be as high as 71.7% among patient admitted to Kassala hospital [14]. The second report showed a very low prevalence of (0.6%) as the study involved participants during dry season of the year where vector transmission is very rare [16]. The two seroepidemiological surveys were conducted in the locality of Kassala.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The seroprevalence data were also higher than what was previously reported from Sudan. Previous studies from Port Sudan, Kassala, West Kordofan and the Northern Province found DENV IgG in 9-49% of the tested sera [12,13,15,16,28] (reviewed in [3]. Together the seroprevalence data indicate that further seroepidemiologic testing and surveillance are needed in Sudan.…”
Section: Discussionmentioning
confidence: 80%
“…Another study reported the seroprevalence of dengue virus in 489 participants in Kassala in the year 2011. A total of 46/489 (9.4%) samples were positive for the dengue virus IgG and IgM using the ELISA assay [228]. In October 2012, the suspected cases of viral hemorrhagic fever were screened for YFV disease.…”
Section: Sudanmentioning
confidence: 99%